Contemporary Fiqh Perspectives on Istihalah: A Case Study of Black Soldier Fly Larvae in Animal Feed Practices in Malaysia and Indonesia - Mohd Sham Kamis; Nik Abdul Rahim Nik Abdul Ghani; Luqman Hakim Satiman; Siong Fong Sim; Syed Ahmed Abdallah (Faculty of Sharia, IAIN Metro, 2025)
This study uses a qualitative research design, which is well-suited for examining problematic jurisprudential arguments within Islamic law. Practically, Indonesia and Malaysia serve as key case studies due to their strict adherence to Shafi'i jurisprudence and the varying interpretations of halal certification bodies such as the Indonesian Ulema Council (MUI) and Malaysia's Department of Islamic Development (JAKIM). The qualitative approach enables an in-depth interpretation of how istihalah (transformation) is analysed in different scholarly traditions and its implications for the permissibility of Black Soldier Fly (BSF) larvae as ruminant feed. A textual analysis approach is adopted to examine classical and contemporary Islamic jurisprudence texts. Specifically, this study uses a qualitative research design, which is well-suited for examining problematic jurisprudential arguments within Islamic law. This qualitative approach enables an in-depth interpretation of how istihalah is analysed in different scholarly traditions and its implications for the permissibility of Black Soldier Fly (BSF) larvae as ruminant feed. The findings related to the Black Soldier Fly (BSF) larvae taken from the sample in Mega BSF Sdn. Bhd, Sibu, Sarawak. The findings were presented at Pejabat Mufti Wilayah Persekutuan, Jabatan Mufti Perlis and Jabatan Mufti Sarawak. Based on the above framework, this study redefines istihalah within modern bioeconomies by introducing empirical degradation thresholds as a basis for juristic rulings—a departure from abstract textual analysis. By mapping BSF’s 4:1 waste-to-biomass efficiency to maqasid alshariah objectives, it advances a replicable framework for addressing emerging food technologies in Islamic law.